Technical synthesis and characterization of nanospherical cadmium oxide/conductive substrate thin films: optical linearity and nonlinearity. (22nd May 2019) - Jafer, Rashida; Yahia, I S
Abstract: A study was conducted on CdO/ITO optical thin film system to analyze the quality of the as-prepared CdO nanostructure for linear and nonlinear optical properties. The CdO/ITO optical thin film system was produced through a very simple sol-gel spin coating technique at certain production parameters. The structural and morphological characters of the studied films were characterized by the well-known x-ray diffraction and atomic force microscopy techniques. A set of linear optical studies was conducted to analyze the absorption, transmittance, and reflectance and then, the absorption and refractive indices were also evaluated from the spectrophotometric data. The dielectric nature of the CdO/ITO optical system was characterized to evaluate the dielectric constant, dielectric loss and dissipation factor. Furthermore, the band gap study was also conducted since this is one of the merits of the prepared materials for their applications in optoelectronics. Finally, a set of nonlinear optical studies was performed, which helped to analyze and characterize the nonlinear nature of the as-prepared CdO/ITO optical thin films. It is found that CdO/ITO is a promising material for optoelectronic applications.